Pendapatan Bagi Petani Sawah Dalam Perspektif Produktivitas Di Desa Pandanan Kecamatan Duduk Sampeyan Gresik - A’isyah, Siti; Santoso, Rahmat Agus (Jurnal Mahasiswa Manajemen, 2021)
Background - The problem faced by farmers in Pandanan village is that the size of the input (resources) is higher than the size of the output (results obtained). The results of this production affect the profits that will be obtained by farmers. Objective - This study aims to analyze the income of farmers in Pandanan Village, Sit Sampeyan Gresik District, from a productivity perspective. Design/Methodology/Approach - By using 5 informants who were interviewed to find the actual income in terms of labor and capital. Testing is done using qualitative research with descriptive analysis method. Findings - The cause of disciplinary action information about weather conditions, interests, time scheduling and family conditions. The cause of disciplinary action by leaving early is unexpected conditions and needs for family needs, employees who do not use shoes when working hours are still ongoing due to weather conditions, healthy conditions, while employees who do not use ID cards are because employees think that the use of ID cards is only used when there is a meeting outside the office. Research implications - This research contributes to examining income from a productivity perspective in terms of labor and capital. Research limitations - This study has limited research focus, namely the meaning of income for farmers in productivity where researchers find about aspects of labor and capital in income for farmers.